Asuhan Keperawatan Nyeri Akut pada Ny. S dengan Hipertensi di Puskesmas Kembaran 1 Banyumas: Acute Pain Nursing Care for Mrs. S with hypertension at the Public Health Center in Kembaran 1 Banyumas - Solikhati, Nuki; Khasanah, Suci; Susanto, Amin (Journal of Nursing Education and Practice, 2023)
Introduction: Hypertension is abnormally high blood pressure. In general, a person who is said to have hypertension if his blood pressure is 140/90 mmHg.   Some of the signs and symptoms that often appear in people with hypertension, namely headaches when awake, blurred vision due to hypertensive damage to the retina, and the way of walking begins to be disturbed due to the beginning of damage to the nervous system. However, the typical signs and symptoms found in hypertensive patients are headaches. Objectives: To describe nursing care in hypertensive patients with acute pain. Method: This research uses qualitative descriptive methods in the form of case studies. Nursing care was provided to Mrs.S during 3 home visits. Data collection techniques were obtained from the results of interviews, observations, and physical examinations. Result: The results of the study found that Mrs. S patient was 57 years old, had an elementary school education, and worked as a housewife. Mrs. S was diagnosed with hypertension with a blood pressure value of 160/100 mmHg. During the assessment, Mrs.S complained of pain in her head 3 days ago. Mrs. S got the drugs amlodipine and antalgin. Based on the data obtained, the patient experiences acute pain. Researchers provided interventions in non-pharmacological administration of warm compress for three days, as well as teaching and explaining to families related to warm compress. Conclusion: The action of a warm compress for 3 days shows a decrease in pain complaints and the patient's pain level, so it can be concluded that the administration of a warm compress is effective for treating pain in patients.